1993
DOI: 10.1002/app.1993.070500212
|View full text |Cite
|
Sign up to set email alerts
|

Monosize polystyrene microbeads by dispersion polymerization

Abstract: SYNOPSISMonosize polystyrene microbeads were prepared by dispersion polymerization in different alcohol/ water media. Azobisisobutyronitrile and polyacrylic acid were utilized as initiator and steric stabilizer, respectively. The polymerizations were performed in three kinds of dispersion media having different polarities: isopropanol/water, 1-butanol/water, and 2-butanol/water. The effects of initiator and stabilizer concentrations, alcohol/water ratio, and monomer /dispersion medium ratio on the size and mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
98
0
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(110 citation statements)
references
References 22 publications
11
98
0
1
Order By: Relevance
“…23,24 One gram of the steric stabilizer was dissolved in the dispersion medium containing 90 mL of ethyl alcohol and 10 mL of water. The monomer phase was prepared by dissolving various amounts of AIBN (70 and 140 mg for HM and LM PS latexes, respectively) in 10 mL of styrene.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…23,24 One gram of the steric stabilizer was dissolved in the dispersion medium containing 90 mL of ethyl alcohol and 10 mL of water. The monomer phase was prepared by dissolving various amounts of AIBN (70 and 140 mg for HM and LM PS latexes, respectively) in 10 mL of styrene.…”
Section: Methodsmentioning
confidence: 99%
“…23,24 The latex from the reactor was centrifuged and the supernatant was removed. The particles were washed with fresh dispersion medium a few times, then distilled water was added and a new dispersion was stirred for 24 h at room temperature to remove any stabilizer remaining on the surface of the polymeric particles.…”
Section: Methodsmentioning
confidence: 99%
“…Crosslinking and adhesion between homogeneous solution, and its change during the polymerization, became recognized as one of the the panels will provide structural strength, and also prevent the movement of slightly off-sized potentially influential factors with respect to the size and monodispersity. Tuncel et al 7 correlated spacer particles. Intensive experiments revealed that the dethe average size of PS particles with the solubility parameter of the medium, and found that the sired monodispersity for the spacers, less than 4% coefficient of variation (CV), was never achieved maximum size was attained at a solubility parameter of 12.5 in mixed solvents of isopropanol, no matter how the compositions of polymerization recipe were changed on the basis of solvent-cosol-1-butanol, 2-butanol, and water.…”
Section: Introductionmentioning
confidence: 97%
“…1 To disperse particles stably, a suitable steric stabilizer was used, such as polyethylene oxide, 2 polyvinylpyrrolidone, 3 poly(2-ethyl-2-oxazoline), 4 hydroxypropyl cellulose, 5 and poly(acrylic acid). 6 Aromatic polyimides (PI) are the most useful super engineering plastics which exhibit excellent thermal, electrical, and mechanical properties, and have been used widely in aerospace, electronics, and other industries. They are generally prepared through a two-step procedure by the ring-opening polyaddition of aromatic diamines to aromatic tetracarboxylic dianhydrides giving poly(amic acid)s (PAA), followed by thermal cyclodehydration.…”
mentioning
confidence: 99%